Prospects of digital transformation in construction - Eriksson Taina; Ertiö Titiana; Lahtinen Roosa; Saarinen Eeli; Saaristo Aino (Turun yliopisto, Kauppakorkeakoulu, 2025)
This report looks into the current situation in the construction industry and provides an analysis of the prospects of digital transformation. The construction industry has lagged behind in the field of digitalisation, with most construction companies still struggling with the early steps of this process. Here, we examine the realities construction site managers, whom we identify as important players in digital transformation, face in their daily work.
The prospects of digital transformation can be looked at from various perspectives, and in this report, we concentrate on three focal angles perceived as related challenges:
1. The unquestioned conventional perceptions of older professionals; 2. The perceived burden of digital tools; 3. Management of the conditions for digital work on site.
By discussing the phenomenon from these angles, we argue that the prospects of digital transformation in construction are significantly impacted by the need for improving quality, involving craftspeople, overcoming discouraging technology experiences, taking ownership of the changing job role and engaging in active upskilling. Digital transformation in construction will materialise sooner rather than later. Therefore, there is urgency in conceptualising the use of digital technologies, first as an integral part of the site managers’ job description and thereafter as part of every construction professional’s daily work. Top management needs to be hands on when it comes to creating the conditions for digital transformation, offering site managers the support needed but also demanding consistent utilisation of suitable digital tools once they have been found.